Consumer interest rates and retail mutual fund flows - Jesus Sierra (Bank of Canada, 2012)
This paper documents a link between the real and financial sides of the economy. We find that retail equity mutual fund flows in Canada are negatively related to current and past changes in a component of the prime and 5-year mortgage rates that is uncorrelated with government rates. The effect is present when we control for other determinants of fund flows and is more pronounced for big and old funds. The results suggest that consumers' investments in domestic equity mutual funds take time to respond to changes in interest rates, and that developments in the market for consumer debt may have spillovers into other areas of the financial services industry.
Keywords: G21; G23; 330; Financial services; Interest rates